Radiosensitivity and the Influence of Gamma Rays Irradiation on Local Samosir Shallots - Mariati Sinuraya; Rosmayati Rosmayati; Hasanuddin Hasanuddin; Diana Sofia Hanafiah (Syiah Kuala University, 2015)
Bulbs of localSamosir Shallot with the weight ranging from 1,3 to1,7 g were irradiated by several doses of gamma rays in order to investigate the radiosensitivity and the effects of irradiatons on the plants. Dry bulbs 2,5 months after harvest were exposed to gamma raysradiation ranging from 0 Gy to 20 Gy to determine their responses to radiation stress and the effective radiation dose for identification of Lethal dose 50 (LD50). Percentage of shoot growth was measured on 35th days after planting. The variation in morphological and agronomic characters were also determined. The results indicated that increasing doses of gamma irradiation had significant effect on shoot growth. Increasing in gamma rays doses from 0 Gy to 11Gy had little effect on percentage of shoot growth.With the increase in radiation dosesabove 11Gy, agreat reduction in percentage of shoot growth was observed in irradiated bulbs as compared to control. The LD50 values of local Samosir Shallot determined from linear regression analysis (using Curve-fit Analysis software) based on percentage of regenerated shoot growth was 11.60 Gy. There were also siqnificantdifferenciesbetweenregenerated plants growth from irradiated bulbs and control (unirradiated).Treated bulbs produced shorther plant lenght and less leave number